Availability of alcohol: Location, time and ease of purchase in high‐ and middle‐income countries: Data from the International Alcohol Control Study. (26th March 2018) - Gray‐Phillip, Gaile; Huckle, Taisia; Callinan, Sarah; Parry, Charles D. H.; Chaiyasong, Surasak; Cuong, Pham Viet; Mackintosh, Anne‐Marie; Meier, Petra; Kazantseva, Elena; Piazza, Marina; Parker, Karl; Casswell, Sally
Abstract: Introduction and Aims: Cross‐country studies on alcohol purchasing and access are rare. We examined where and when people access alcohol to understand patterns of availability across a range of middle‐ and high‐income countries. Design and Methods: Surveys of drinkers in the International Alcohol Control study in high‐income countries (Australia, England, Scotland, New Zealand and St Kitts and Nevis) and middle‐income countries (Mongolia, South Africa, Peru, Thailand and Vietnam) were analysed. Measures were: location of purchase from on‐premise and take‐away outlets, proportion of alcohol consumed on‐premise versus take‐away outlets, hours of purchase, access among underage drinkers and time to access alcohol. Results: On‐premise purchasing was prevalent in the high‐income countries. However, the vast majority of alcohol consumed in all countries, except St Kitts and Nevis (high‐income), was take‐away. Percentages of drinkers purchasing from different types of on‐premise and take‐away outlets varied between countries. Late purchasing was common in Peru and less common in Thailand and Vietnam. Alcohol was easily accessed by drinkers in all countries, including underage drinkers in the middle‐income countries. Discussion and Conclusions: In nine out of 10 countries the vast majority of alcohol consumed was take‐away. Alcohol was readily available and relatively easy for underage drinkers to access, particularly in the middle‐income countries. Research is needed to assess the harms associated with take‐away consumption including late at night. Attention is needed to address the easy access by underage drinkers in the middle‐income countries which has been less of a focus than in high‐income countries.